Sustainable urban and regional infrastructure development : technologies, applications and management - Yigitcanlar, Tan (Premier Reference source, 2010)
The concept of ‘sustainability’ has been pushed to the forefront of policy-making and politics as the world wakes up to the impacts of climate change and the effects of the modern urban lifestyle.Sustainable Urban and Regional Infrastructure Development: Technologies, Applications and Management,bridges the gap in the current literature by addressing the overall problems present in society's major infrastructures, and the technologies that may be applied to overcome these problems. It focuses on ways in which energy intensive but ‘invisible’ (to the general public) facilities can become green or greener. The studies presented are lessons to be learnt from our neighbors and from our own backyard, and provide an excellent general overview of the issues facing us all